Bayesian Analysis for Two Parameter Lomax Distribution Under Different Loss Functions - Kumari, Pavitra; Kumar, Vinay; Aditi (Communications in Mathematics and Applications, 2022)
Statistical analysis via Bayesian approach is a common practice applied to draw inference about unknown parameter(s) and reliability characteristics of the probability distribution. The article include Bayesian inference of unknown shape parameter of two-parameter Lomax distribution. An attempt has been made to obtain Bayes estimators by using extension of Jeffrey’s prior and Gamma prior under Entropy loss function and Precautionary loss function. Comparison has been made by using mean square error through simulation study with varying sample sizes.